Arsenene nanoribbon edge-resolved strong magnetism - Wang, Sanmei (2020)
We proposed a mechanism to induce strong magnetism of up to 10.92 emu g-1 in hexagonal-phase arsenene nanoribbon (AsNR) from the perspective of edge quantum entrapment. Consistency between bond-order-length-strength correlation (BOLS) theory and density functional theory (DFT) calculations verified that: (i) the edge bond contraction of 9.54% deepened the edge potential well of AsNR, (ii) a net charge of 0.06 e- transferred from the inner region to the edge; and (iii) the edge quantum well polarized the unpaired electron and the net spin (antiferromagnetic or ferromagnetic depending on the width) is localized at the zigzag edge. The finding sheds a light on applications of AsNR in magnetic storage devices.